Legal Responbility for Violations in the Appointment of Foundation Management (A Study of Decision No.454/Pdt.G/2022/Pn.Mdn) - Farah Kamila, Balqis; Andryan2, Andryan (Dinasti Research, 2024)
A foundation is a legal entity that has a management structure to oversee its activities. Serving as an organ of the foundation's legal body is not easy; every action taken by the management must be based on the Foundation's Articles of Association/House Rules and must not exceed the authority granted, in accordance with the provisions of the foundation law. Therefore, if there are multiple decisions regarding the appointment and management of the foundation, they must comply with the applicable regulations, raising concerns if there is more than one decision with different issuances. This research aims to understand the Position and Legal Responsibility of Foundation Managers, the Procedure for the Appointment and Ratification of Foundation Managers Based on Foundation Law, and the validity of the Decision Letter Regarding the Appointment and Ratification of the Foundation's Management Body Based on Decision Number 454/Pdt.G/2022/PN.Mdn. This study employs a normative legal approach, using secondary data (through literature study) and primary, secondary, and tertiary legal materials. Furthermore, the data is analyzed qualitatively from a legal perspective. The results of this research indicate that the procedures for the appointment and dismissal of foundation administrators in Indonesia are regulated by the foundation's Articles of Association (AD) and Bylaws (ART), as well as applicable legal provisions, particularly in Law Number 16 of 2001 concerning Foundations and its amendments in Law Number 28 of 2004. If the party issuing the decision does so in violation of these regulations, it can be considered an unlawful act and is liable for damages resulting from such actions.